Lazaro Papazian : história, acervo e patrimônio - Siqueira, Silvano da Silva (2014)
Lázaro Papazian (107-1991) was a photographer and a filmmaker of Armenian origin who in 1926 came to Cuiabá and here it was. He was in the city of Cuiabá many crafts, such as tenant of the Hotel Termas Warm Waters, technical and managerial capacity of football team, director and writer of newspapers, athlete and arbitrator of boxing and owner of cinemas. In this dissertation we highlight its action as a photographer which provided for the formation of your photo collection over the course of more than 50 years of photographic records in the city of Cuiabá, and from de analysis of a thematic block this acquis, understand the potential that this has. It was necessary to trace the steps of our character Lázaro Papazian of Everan in Armênia for the city of Cuiabá and his experience as a photographer in the city of Cuiabá. After his death in 1991, his collection has continued to “walk”, carrying out its own path of life, faced abandonment, fire and flood (but survived) and at this moment it is allocated at the Museum of Image and Sound at Cuiabá, passing among other difficulties, problems of physical order-structural. From the Acquis Communautaire Lázaro Papazian this dissertation intends to make a call to issues that involve the problem of discontinuity of public policies cultural facing collections and museums not only of Cuiabá as from all over Brazil.